Depth migration of crustal-scale seismic reflection profiles: A case study in the Bohai Bay basin - Deng, Xiaofan; Li, Hongqiang; Gao, Rui (Frontiers in Earth Science, 2023)
The application of the pre-stack depth migration (PSDM) method using deep seismic reflection data is still a challenge. In this paper, a deep seismic reflection dataset collected from the Bohai Bay Basin is used to test the applicability of the PSDM method. After improving the signal-to-noise ratio of the prestack gathers and building an accurate velocity model capturing lateral and vertical variations, a high-quality PSDM profile is obtained. This profile shows detailed crustal structures and an undulating Moho. The depth difference between the east and west sides of the Moho imaged in the profile is about 6 km. The Moho is disrupted by several discontinuities. Compared with conventionally stacked time-migration profiles, the PSDM profile provides a higher-resolution subsurface image with accurate depth information. Combining geological and geophysical data, the PSDM profile reveals geologic structures responsible for crust thinning during the destruction of the North China Craton. The profile also provides more accurate depth domain information for further study of crust-mantle interaction in this area.